SIMULATION ET SPATIALISATION DU RISQUE D’INONDATION DANS UNE VALLEE ANTHROPISEE. LE CAS DE LA VALLEE DE L’OURIKA (HAUT ATLAS, MAROC) - Abdelhafid El Alaoui El Fels; Mohamed El Mehdi Saidi (European Scientific Journal, ESJ, 2014)
This work is devoted to the simulation and spacialisation of natural flows at the Ourika Valley in Morocco. Subject to climatic and anthropogenic forcing, the valley's flood flows are, nowadays, extremely high compared to the average flow. Decadal and centennial floods simulation was undertaken using two software solutions. The floodplains mapping gives valuable information related to the magnitude of the overflow affecting fields, buildings and the road, leading to Marrakech, along the river banks. Knowing that the Ourika Valley is narrow, heavily populated with a unique road to Marrakech, this work reveals the amplitude of flooding risks in this area. That’s why, regular human activities must be regulated and the risks must be managed by preventing and forecasting.